The Influence of Industrial Type, Media Exposure and Institutional Ownership on Carbon Emission Disclosure - Haura, Salma; Willy Sri Yuliandhari (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
The implementation of carbon emission disclosure is a solution that companies can use to reduce carbon emissions and ensure that they carry out business activities in a socially and environmentally responsible manner. The phenomenon that occurs in this study is that several companies in the basic materials sector have not fully carried out carbon emission disclosure every year because carbon emission disclosure in Indonesia is still voluntary. This study aims to simultaneously and partially determine the effect of industrial type, media exposure, and institutional ownership on carbon emission disclosure in basic materials sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. This study uses a quantitative method with a sample selection method, namely purposive sampling. The analysis model used in this study is a multiple linear regression analysis model using SPSS 26 software. The results state that industrial type and media exposure have a positive and significant effect on carbon emission disclosure. Institutional ownership has a negative and significant effect on carbon emission disclosure.